Powder metallurgy shaft part material and preparation method thereof
Through the combination and process of powder metallurgy materials with specific ratios, the problem of insufficient performance of existing powder metallurgy shaft parts is solved, and the mechanical properties, wear resistance, fatigue resistance and corrosion resistance are significantly improved. It is suitable for Industrial application.
Patent Information
- Application Number
- CN202411460644.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-14
AI Technical Summary
The existing powder metallurgical shaft-type materials still have room for improvement in mechanical mechanical properties, wear resistance, fatigue resistance and corrosion resistance, and it is difficult to meet industrial needs.
Use a combination of powder metallurgical materials with specific ratios, including manganese powder, copper powder, molybdenum powder, nickel powder, rare earth powder, rhenium powder, osmium powder, vanadium powder, tantalum powder, cobalt powder, non-metal powder, nano-titanium nitride, Components such as nanochromium boride and nanotungsten carbide, and powder metallurgy shaft-type parts materials with excellent performance are obtained through mixing, pressing, sintering and heat treatment.
It significantly improves the mechanical and mechanical properties, wear resistance, fatigue resistance and corrosion resistance of powder metallurgical shaft parts materials, and has a simple process and low energy consumption. It is suitable for large-scale production and extends its service life.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder metallurgy, and in particular to a powder metallurgy shaft part material and a preparation method thereof. Background Art
[0002] With the continuous advancement of global industrialization, the use of shaft parts in industry is becoming more and more important. Shaft parts are one of the typical parts often encountered in machines. They are mainly used to support transmission parts, transmit torque and bear loads. The ideal shaft parts material needs to have not only excellent mechanical properties, but also good wear resistance, fatigue resistance and corrosion resistance.
[0003] At present, shaft parts are usually made by powder metallurgy. Powder metallurgy is an industrial technology that produces metal powder or uses metal powder (or a mixture of metal powder and non-metallic powder) as raw material, and then forms and sinters it to produce metal materials, composite materials and various types of products. It has a series of advantages such as significant energy saving, material saving, excellent performance, high product precision and good stability, and is very suitable for mass production. However, the shaft parts materials currently made by powder metallurgy technology still have defects in mechanical properties, wear resistance, fatigue resistance and corrosion resistance, which still need to be further improved.
[0004] In order to solve the above problems, the Chinese invention patent with authorization announcement number CN103406532B discloses a powder metallurgy material for automobile shaft parts and its preparation method, which is made of the following raw materials in parts by weight: iron powder 93-94, chromium powder 1.2-1.4, molybdenum powder 0.3-0.4, manganese sulfide 0.8-1.0, copper 0.4-0.6, nickel powder 0.3-0.4, microcrystalline wax 1-2, SnO 2 1.2-1.3, V 2 O 5 0.5-0.7, Nb 0.06-0.08, tungsten carbide 0.4-0.6, TiC 0.3-0.5, hafnium diboride 0.1-0.2, dispersant 2-3, stearic acid 2-3. The addition of chromium powder in the formula of the invention significantly improves the hardness, wear resistance, impact resistance, corrosion resistance and wear resistance of the shaft parts at high temperatures. After cutting, the dimensional accuracy and surface roughness of the cutting surface are guaranteed to be good. However, its fatigue resistance, wear resistance and corrosion resistance still need to be further improved.
[0005] It can be seen that the development of a powder metallurgy shaft parts material with excellent mechanical properties, wear resistance, fatigue resistance and corrosion resistance and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the field of powder metallurgy shaft parts materials. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a powder metallurgy shaft parts material having excellent mechanical properties, wear resistance, fatigue resistance and corrosion resistance and a preparation method thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is: a powder metallurgy shaft parts material is made of the following components in weight percentage: manganese powder 0.5wt%-1wt%, copper powder 1wt%-2wt%, molybdenum powder 0.1wt%-0.4wt%, nickel powder 1wt%-3wt%, hafnium powder 0.03wt%-0.06wt%, rare earth powder 0.03wt%-0.06wt%, rhenium powder 0.001wt%-0.004wt%, osmium powder 0.001wt%-0.003wt%, vanadium powder 0.1wt%-0.06wt% t%-0.3wt%, tantalum powder 0.01wt%-0.03wt%, cobalt powder 0.3wt%-0.5wt%, non-metallic powder 0.001wt%-0.003wt%, indium powder 0.01wt%-0.04wt%, germanium powder 0.01wt%-0.03wt%, gallium powder 0.05wt%-0.12wt%, nano-titanium nitride 0.01wt%-0.03wt%, nano-chromium boride 0.01wt%-0.03wt%, nano-tungsten carbide 0.01wt%-0.03wt%, and the balance is iron powder.
[0008] Preferably, the powder metallurgy shaft parts material also includes the following components in weight percentage: lubricant 0.01wt%-0.06wt%, cellulose nanocrystals 0.08wt%-0.12wt%, trirosin acid glycerol 0.05wt%-0.1wt%, 1,3,5-triglycidyl-S-triazinetrione 0.1wt%-0.15wt%.
[0009] Preferably, the lubricant is zinc stearate.
[0010] Preferably, the fiber nanocrystals have a length of 100-500 nm and a diameter of 20-100 nm, and are provided by Beijing Nanosun Technology Co., Ltd.
[0011] Preferably, the particle size of the manganese powder is 800-1200 mesh; the particle size of the copper powder is 1000-1300 mesh; the particle size of the molybdenum powder is 1200-1500 mesh; the particle size of the nickel powder is 800-1000 mesh; the particle size of the hafnium powder is 800-1200 mesh; the particle size of the rare earth powder is 1000-1300 mesh; the particle size of the rhenium powder is 900-1300 mesh; the particle size of the osmium powder is 1200-1400 mesh; the particle size of the vanadium powder is 1100-1400 mesh; and the particle size of the tantalum powder is 1000-1300 mesh.
[0012] Preferably, the particle size of the cobalt powder is 900-1300 mesh; the particle size of the non-metallic powder is 1200-1400 mesh; the particle size of the indium powder is 1100-1400 mesh; the particle size of the germanium powder is 1000-1300 mesh; the particle size of the gallium powder is 800-1000 mesh; and the particle size of the iron powder is 1000-1400 mesh.
[0013] Preferably, the particle size of the nano-chromium boride is 10-80 nm; the particle size of the nano-titanium nitride is 20-90 nm; and the particle size of the nano-tungsten carbide is 30-70 nm.
[0014] Preferably, the non-metallic powder is a mixture of silicon powder, boron powder and tellurium powder in a mass ratio of 1:(0.8-1.2):(0.2-0.5).
[0015] Preferably, the rare earth powder is a mixture of scandium powder, yttrium powder and cerium powder in a mass ratio of 1:(1-2):(2-4).
[0016] Another object of the present invention is to provide a method for preparing the powder metallurgy shaft parts material, comprising the following steps:
[0017] Step S1, putting each component into a mixer according to mass percentage and mixing them evenly to obtain a powder metallurgy mixed raw material powder;
[0018] Step S2, loading the powder metallurgy mixed raw material powder into a mold, pressing to obtain a compact, and then sintering in a vacuum atmosphere;
[0019] Step S3: After heat treatment, powder metallurgy shaft parts material is obtained.
[0020] Preferably, the pressing pressure in step S2 is 280-530 MPa.
[0021] Preferably, the sintering in step S2 is hot pressing sintering, the sintering temperature is 1220-1360° C., the holding time is 2-4 hours, and the pressure applied to the mold is 15-25 MPa.
[0022] Preferably, the heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching is a two-stage quenching, the temperature of the first stage quenching is 700-750°C, the holding time is 30-45 minutes, the temperature of the second stage quenching is 950-1100°C, the holding time is 1-2 hours, and oil cooling to room temperature; the temperature of the tempering is 350-500°C, and the holding time is 1-3 hours.
[0023] Due to the application of the above technical solution, the present invention has the following beneficial effects:
[0024] (1) The method for preparing powder metallurgy shaft parts materials disclosed in the present invention does not require special equipment, has low capital investment, low energy consumption, high preparation efficiency and finished product qualification rate, simple process, convenient operation and control, low labor intensity, small impact on the environment, is suitable for continuous large-scale production, and has high promotion and application value.
[0025] (2) The powder metallurgy shaft parts material disclosed in the present invention is made of the following components in percentage by weight: 0.5wt%-1wt% manganese powder, 1wt%-2wt% copper powder, 0.1wt%-0.4wt% molybdenum powder, 1wt%-3wt% nickel powder, 0.03wt%-0.06wt% hafnium powder, 0.03wt%-0.06wt% rare earth powder, 0.001wt%-0.004wt% rhenium powder, 0.001wt%-0.003wt% osmium powder, 0.1wt%-0.3wt% vanadium powder. t%, tantalum powder 0.01wt%-0.03wt%, cobalt powder 0.3wt%-0.5wt%, non-metallic powder 0.001wt%-0.003wt%, indium powder 0.01wt%-0.04wt%, germanium powder 0.01wt%-0.03wt%, gallium powder 0.05wt%-0.12wt%, nano titanium nitride 0.01wt%-0.03wt%, nano chromium boride 0.01wt%-0.03wt%, nano tungsten carbide 0.01wt%-0.03wt%, and the balance is iron powder. Through the reasonable selection of the types and dosage ratios of each component, they can better play a role in cooperation with each other, giving the product excellent mechanical properties, wear resistance, fatigue resistance and corrosion resistance.
[0026] (3) The powder metallurgy shaft parts material disclosed in the present invention further comprises the following components by weight percentage: 0.01wt%-0.06wt% lubricant, 0.08wt%-0.12wt% cellulose nanocrystals, 0.05wt%-0.1wt% trirosin acid glycerol, 0.1wt%-0.15wt% 1,3,5-triglycidyl-S-triazinetrione. These components can effectively improve the compatibility between powder metallurgy raw material powders, increase the density of the internal structure, and further improve the mechanical properties, wear resistance, fatigue resistance and corrosion resistance of the product.
[0027] (4) The powder metallurgy shaft parts material disclosed in the present invention has better performance, more stable performance and longer service life through reasonable selection of process parameters during the preparation process. DETAILED DESCRIPTION
[0028] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations.
[0029] Example 1
[0030] A powder metallurgy shaft parts material is made of the following components in percentage by weight: 0.5wt% manganese powder, 1wt% copper powder, 0.1wt% molybdenum powder, 1wt% nickel powder, 0.03wt% hafnium powder, 0.03wt% rare earth powder, 0.001wt% rhenium powder, 0.001wt% osmium powder, 0.1wt% vanadium powder, 0.01wt% tantalum powder, 0.3wt% cobalt powder, 0.001wt% non-metal powder, 0.01wt% indium powder, 0.01wt% germanium powder, 0.05wt% gallium powder, 0.01wt% nano titanium nitride, 0.01wt% nano chromium boride, 0.01wt% nano tungsten carbide, and the balance is iron powder.
[0031] The powder metallurgy shaft parts material also includes the following components in weight percentage: 0.01wt% lubricant, 0.08wt% cellulose nanocrystals, 0.05wt% trirosin acid glycerol, and 0.1wt% 1,3,5-triglycidyl-S-triazinetrione; the lubricant is zinc stearate; the fiber nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.
[0032] The particle size of the manganese powder is 800 mesh; the particle size of the copper powder is 1000 mesh; the particle size of the molybdenum powder is 1200 mesh; the particle size of the nickel powder is 800 mesh; the particle size of the hafnium powder is 800 mesh; the particle size of the rare earth powder is 1000 mesh; the particle size of the rhenium powder is 900 mesh; the particle size of the osmium powder is 1200 mesh; the particle size of the vanadium powder is 1100 mesh; and the particle size of the tantalum powder is 1000 mesh.
[0033] The particle size of the cobalt powder is 900 mesh; the particle size of the non-metallic powder is 1200 mesh; the particle size of the indium powder is 1100 mesh; the particle size of the germanium powder is 1000 mesh; the particle size of the gallium powder is 800 mesh; the particle size of the iron powder is 1000 mesh; the particle size of the nano-chromium boride is 10nm; the particle size of the nano-titanium nitride is 20nm; and the particle size of the nano-tungsten carbide is 30nm.
[0034] The non-metallic powder is a mixture of silicon powder, boron powder and tellurium powder in a mass ratio of 1:0.8:0.2; the rare earth powder is a mixture of scandium powder, yttrium powder and cerium powder in a mass ratio of 1:1:2.
[0035] A method for preparing the powder metallurgy shaft parts material comprises the following steps:
[0036] Step S1, putting each component into a mixer according to mass percentage and mixing them evenly to obtain a powder metallurgy mixed raw material powder;
[0037] Step S2, loading the powder metallurgy mixed raw material powder into a mold, pressing to obtain a compact, and then sintering in a vacuum atmosphere;
[0038] Step S3: After heat treatment, powder metallurgy shaft parts material is obtained.
[0039] The pressing pressure in step S2 is 280 MPa; the sintering in step S2 is hot pressing sintering, the sintering temperature is 1220° C., the holding time is 2 h, and the pressure applied to the mold is 15 MPa.
[0040] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching is a two-stage quenching, the temperature of the first stage quenching is 700°C, the holding time is 30 minutes, the temperature of the second stage quenching is 950°C, the holding time is 1 hour, and oil cooling to room temperature; the temperature of the tempering is 350°C, and the holding time is 1 hour.
[0041] Example 2
[0042] A powder metallurgy shaft parts material is made of the following components in percentage by weight: 0.6wt% of manganese powder, 1.2wt% of copper powder, 0.2wt% of molybdenum powder, 1.5wt% of nickel powder, 0.04wt% of hafnium powder, 0.04wt% of rare earth powder, 0.002wt% of rhenium powder, 0.0015wt% of osmium powder, 0.15wt% of vanadium powder, 0.015wt% of tantalum powder, 0.35wt% of cobalt powder, 0.0015wt% of non-metallic powder, 0.02wt% of indium powder, 0.015wt% of germanium powder, 0.07wt% of gallium powder, 0.015wt% of nano titanium nitride, 0.015wt% of nano chromium boride, 0.015wt% of nano tungsten carbide, and the balance is iron powder.
[0043] The powder metallurgy shaft parts material also includes the following components in weight percentage: 0.035wt% lubricant, 0.1wt% cellulose nanocrystals, 0.075wt% trirosin acid glycerol, and 0.13wt% 1,3,5-triglycidyl-S-triazinetrione; the lubricant is zinc stearate; the fiber nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.
[0044] The particle size of the manganese powder is 900 mesh; the particle size of the copper powder is 1100 mesh; the particle size of the molybdenum powder is 1300 mesh; the particle size of the nickel powder is 900 mesh; the particle size of the hafnium powder is 900 mesh; the particle size of the rare earth powder is 1100 mesh; the particle size of the rhenium powder is 1000 mesh; the particle size of the osmium powder is 1250 mesh; the particle size of the vanadium powder is 1200 mesh; and the particle size of the tantalum powder is 1100 mesh.
[0045] The particle size of the cobalt powder is 1000 mesh; the particle size of the non-metallic powder is 1250 mesh; the particle size of the indium powder is 1150 mesh; the particle size of the germanium powder is 1100 mesh; the particle size of the gallium powder is 850 mesh; the particle size of the iron powder is 1100 mesh; the particle size of the nano-chromium boride is 30nm; the particle size of the nano-titanium nitride is 30nm; the particle size of the nano-tungsten carbide is 40nm; the non-metallic powder is a mixture of silicon powder, boron powder, and tellurium powder in a mass ratio of 1:0.9:0.3; the rare earth powder is a mixture of scandium powder, yttrium powder, and cerium powder in a mass ratio of 1:1.3:2.5.
[0046] A method for preparing the powder metallurgy shaft parts material comprises the following steps:
[0047] Step S1, putting each component into a mixer according to mass percentage and mixing them evenly to obtain a powder metallurgy mixed raw material powder;
[0048] Step S2, loading the powder metallurgy mixed raw material powder into a mold, pressing to obtain a compact, and then sintering in a vacuum atmosphere;
[0049] Step S3: After heat treatment, powder metallurgy shaft parts material is obtained.
[0050] The pressing pressure in step S2 is 330 MPa; the sintering in step S2 is hot pressing sintering, the sintering temperature is 1260° C., the holding time is 2.5 h, and the pressure applied to the mold is 18 MPa.
[0051] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching is a two-stage quenching, the temperature of the first stage quenching is 720°C, the holding time is 35 minutes, the temperature of the second stage quenching is 1000°C, the holding time is 1.2 hours, and oil cooling to room temperature; the temperature of the tempering is 380°C, and the holding time is 1.5 hours.
[0052] Example 3
[0053] A powder metallurgy shaft parts material is made of the following components in percentage by weight: 0.8wt% manganese powder, 1.5wt% copper powder, 0.25wt% molybdenum powder, 2wt% nickel powder, 0.045wt% hafnium powder, 0.045wt% rare earth powder, 0.0025wt% rhenium powder, 0.002wt% osmium powder, 0.2wt% vanadium powder, 0.02wt% tantalum powder, 0.4wt% cobalt powder, 0.002wt% non-metal powder, 0.025wt% indium powder, 0.02wt% germanium powder, 0.09wt% gallium powder, 0.02wt% nano titanium nitride, 0.02wt% nano chromium boride, 0.02wt% nano tungsten carbide, and the balance is iron powder.
[0054] The powder metallurgy shaft parts material also includes the following components in weight percentage: 0.04wt% lubricant, 0.1wt% cellulose nanocrystals, 0.08wt% trirosin acid glycerol, and 0.13wt% 1,3,5-triglycidyl-S-triazinetrione; the lubricant is zinc stearate; the fiber nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.
[0055] The particle size of the manganese powder is 1000 mesh; the particle size of the copper powder is 1150 mesh; the particle size of the molybdenum powder is 1350 mesh; the particle size of the nickel powder is 900 mesh; the particle size of the hafnium powder is 1000 mesh; the particle size of the rare earth powder is 1150 mesh; the particle size of the rhenium powder is 1100 mesh; the particle size of the osmium powder is 1300 mesh; the particle size of the vanadium powder is 1250 mesh; and the particle size of the tantalum powder is 1150 mesh.
[0056] The particle size of the cobalt powder is 1100 mesh; the particle size of the non-metallic powder is 1300 mesh; the particle size of the indium powder is 1250 mesh; the particle size of the germanium powder is 1150 mesh; the particle size of the gallium powder is 900 mesh; the particle size of the iron powder is 1200 mesh; the particle size of the nano-chromium boride is 50nm; the particle size of the nano-titanium nitride is 60nm; and the particle size of the nano-tungsten carbide is 50nm.
[0057] The non-metallic powder is formed by mixing silicon powder, boron powder and tellurium powder in a mass ratio of 1:1:0.35; the rare earth powder is formed by mixing scandium powder, yttrium powder and cerium powder in a mass ratio of 1:1.5:3.
[0058] A method for preparing the powder metallurgy shaft parts material comprises the following steps:
[0059] Step S1, putting each component into a mixer according to mass percentage and mixing them evenly to obtain a powder metallurgy mixed raw material powder;
[0060] Step S2, loading the powder metallurgy mixed raw material powder into a mold, pressing to obtain a compact, and then sintering in a vacuum atmosphere;
[0061] Step S3: After heat treatment, powder metallurgy shaft parts material is obtained.
[0062] The pressing pressure in step S2 is 410 MPa; the sintering in step S2 is hot pressing sintering, the sintering temperature is 1290° C., the holding time is 3 h, and the pressure applied to the mold is 20 MPa.
[0063] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching is a two-stage quenching, the temperature of the first stage quenching is 730°C, the holding time is 38 minutes, the temperature of the second stage quenching is 1020°C, the holding time is 1.5 hours, and oil cooling to room temperature; the temperature of the tempering is 420°C, and the holding time is 2 hours.
[0064] Example 4
[0065] A powder metallurgy shaft parts material is made of the following components in percentage by weight: 0.9wt% manganese powder, 1.8wt% copper powder, 0.35wt% molybdenum powder, 2.5wt% nickel powder, 0.055wt% hafnium powder, 0.05wt% rare earth powder, 0.0035wt% rhenium powder, 0.0025wt% osmium powder, 0.25wt% vanadium powder, 0.025wt% tantalum powder, 0.45wt% cobalt powder, 0.0025wt% non-metal powder, 0.035wt% indium powder, 0.025wt% germanium powder, 0.11wt% gallium powder, 0.025wt% nano titanium nitride, 0.025wt% nano chromium boride, 0.025wt% nano tungsten carbide, and the balance is iron powder.
[0066] The powder metallurgy shaft parts material also includes the following components in weight percentage: 0.05wt% lubricant, 0.11wt% cellulose nanocrystals, 0.09wt% trirosin acid glycerol, and 0.14wt% 1,3,5-triglycidyl-S-triazinetrione; the lubricant is zinc stearate; the fiber nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.
[0067] The particle size of the manganese powder is 1100 mesh; the particle size of the copper powder is 1250 mesh; the particle size of the molybdenum powder is 1450 mesh; the particle size of the nickel powder is 950 mesh; the particle size of the hafnium powder is 1100 mesh; the particle size of the rare earth powder is 1250 mesh; the particle size of the rhenium powder is 1200 mesh; the particle size of the osmium powder is 1350 mesh; the particle size of the vanadium powder is 1350 mesh; and the particle size of the tantalum powder is 1250 mesh.
[0068] The particle size of the cobalt powder is 1250 mesh; the particle size of the non-metallic powder is 1350 mesh; the particle size of the indium powder is 1350 mesh; the particle size of the germanium powder is 1250 mesh; the particle size of the gallium powder is 950 mesh; the particle size of the iron powder is 1350 mesh; the particle size of the nano-chromium boride is 70nm; the particle size of the nano-titanium nitride is 80nm; the particle size of the nano-tungsten carbide is 60nm; the non-metallic powder is a mixture of silicon powder, boron powder, and tellurium powder in a mass ratio of 1:1.1:0.35; the rare earth powder is a mixture of scandium powder, yttrium powder, and cerium powder in a mass ratio of 1:1.5:3.
[0069] A method for preparing the powder metallurgy shaft parts material comprises the following steps:
[0070] Step S1, putting each component into a mixer according to mass percentage and mixing them evenly to obtain a powder metallurgy mixed raw material powder;
[0071] Step S2, loading the powder metallurgy mixed raw material powder into a mold, pressing to obtain a compact, and then sintering in a vacuum atmosphere;
[0072] Step S3: After heat treatment, powder metallurgy shaft parts material is obtained.
[0073] The pressing pressure in step S2 is 510 MPa; the sintering in step S2 is hot pressing sintering, the sintering temperature is 1340° C., the holding time is 3.5 h, and the pressure applied to the mold is 23 MPa.
[0074] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching is a two-stage quenching, the temperature of the first stage quenching is 740°C, the holding time is 43 minutes, the temperature of the second stage quenching is 1090°C, the holding time is 1.8 hours, and oil cooling to room temperature; the temperature of the tempering is 480°C, and the holding time is 2.5 hours.
[0075] Example 5
[0076] A powder metallurgy shaft parts material is made of the following components in percentage by weight: 1wt% manganese powder, 2wt% copper powder, 0.4wt% molybdenum powder, 3wt% nickel powder, 0.06wt% hafnium powder, 0.06wt% rare earth powder, 0.004wt% rhenium powder, 0.003wt% osmium powder, 0.3wt% vanadium powder, 0.03wt% tantalum powder, 0.5wt% cobalt powder, 0.003wt% non-metal powder, 0.04wt% indium powder, 0.03wt% germanium powder, 0.12wt% gallium powder, 0.03wt% nano titanium nitride, 0.03wt% nano chromium boride, 0.03wt% nano tungsten carbide, and the balance is iron powder.
[0077] The powder metallurgy shaft parts material also includes the following components in weight percentage: 0.06wt% lubricant, 0.12wt% cellulose nanocrystals, 0.1wt% trirosin acid glyceryl ester, and 0.15wt% 1,3,5-triglycidyl-S-triazinetrione; the lubricant is zinc stearate; the fiber nanocrystals have a length of 100-500nm and a diameter of 20-100nm, and are provided by Beijing Naxun Technology Co., Ltd.
[0078] The particle size of the manganese powder is 1200 mesh; the particle size of the copper powder is 1300 mesh; the particle size of the molybdenum powder is 1500 mesh; the particle size of the nickel powder is 1000 mesh; the particle size of the hafnium powder is 1200 mesh; the particle size of the rare earth powder is 1300 mesh; the particle size of the rhenium powder is 1300 mesh; the particle size of the osmium powder is 1400 mesh; the particle size of the vanadium powder is 1400 mesh; and the particle size of the tantalum powder is 1300 mesh.
[0079] The particle size of the cobalt powder is 1300 mesh; the particle size of the non-metallic powder is 1400 mesh; the particle size of the indium powder is 1400 mesh; the particle size of the germanium powder is 1300 mesh; the particle size of the gallium powder is 1000 mesh; the particle size of the iron powder is 1400 mesh; the particle size of the nano-chromium boride is 80nm; the particle size of the nano-titanium nitride is 90nm; the particle size of the nano-tungsten carbide is 70nm; the non-metallic powder is a mixture of silicon powder, boron powder, and tellurium powder in a mass ratio of 1:1.2:0.5; the rare earth powder is a mixture of scandium powder, yttrium powder, and cerium powder in a mass ratio of 1:2:4.
[0080] A method for preparing the powder metallurgy shaft parts material comprises the following steps:
[0081] Step S1, putting each component into a mixer according to mass percentage and mixing them evenly to obtain a powder metallurgy mixed raw material powder;
[0082] Step S2, loading the powder metallurgy mixed raw material powder into a mold, pressing to obtain a compact, and then sintering in a vacuum atmosphere;
[0083] Step S3: After heat treatment, powder metallurgy shaft parts material is obtained.
[0084] The pressing pressure in step S2 is 530 MPa; the sintering in step S2 is hot pressing sintering, the sintering temperature is 1360° C., the holding time is 4 hours, and the pressure applied to the mold is 25 MPa.
[0085] The heat treatment in step S3 includes quenching and tempering performed in sequence; the quenching is a two-stage quenching, the temperature of the first stage quenching is 750°C, the holding time is 45 minutes, the temperature of the second stage quenching is 1100°C, the holding time is 2 hours, and oil cooling to room temperature; the temperature of the tempering is 500°C, and the holding time is 3 hours.
[0086] Comparative Example 1
[0087] A powder metallurgy shaft parts material and a preparation method thereof are basically the same as those of Example 1, except that rhenium powder, osmium powder, nano-titanium nitride and cellulose nanocrystals are not added.
[0088] Comparative Example 2
[0089] A powder metallurgy shaft parts material and a preparation method thereof are basically the same as those of Example 1, except that no non-metallic powder, germanium powder, nano-chromium boride and trirosin acid glycerol are added.
[0090] In order to further illustrate the beneficial technical effects of the powder metallurgy shaft parts materials involved in each embodiment of the present invention, relevant performance tests were conducted on the powder metallurgy shaft parts materials involved in Examples 1-5 and Comparative Examples 1-2; the test methods are as follows:
[0091] (1) Tensile strength: Tested in accordance with standard GB / T228-2002 “Room temperature tensile test method for metal materials”.
[0092] (2) Corrosion resistance: The powder metallurgy shaft parts are subjected to a salt spray corrosion test at a test temperature of 35°C. A 5% mass concentration sodium chloride aqueous solution is sprayed in the test chamber to simulate the accelerated corrosion environment. The powder metallurgy shaft parts are qualified for corrosion resistance if their tolerance time (i.e., the time they remain rust-free) exceeds 1000 hours. Otherwise, they are unqualified.
[0093] (3) Wear resistance: The friction and wear test of each powder metallurgy shaft parts material sample was carried out using a MFT-R4000 high-speed reciprocating friction and wear tester. The test load was 30N, the test time was 5min, and the friction length was 5×10 - 3 m, the friction ball is Al 2 O 3 The wear mass of the material is measured and the wear rate is obtained by calculation. The calculation formula of the wear rate W is as follows: W = m / N·L, where W is the wear rate (g / N·m); m is the wear mass (g); N is the load (N); and L is the total stroke (m).
[0094] (4) Fatigue resistance: The specimens were subjected to a constant amplitude fatigue test (maximum load 100 MPa, minimum load 20 MPa) on an Amsler HFP-422 high frequency fatigue testing machine, and the fatigue life was recorded and counted.
[0095] Table 1
[0096] project tensile strength Wear rate Corrosion resistance Fatigue life unit MPa <![CDATA[×10 -10 g / N·m]]> — Ten thousand times Example 1 1275 0.10 qualified 17.5 Example 2 1286 0.07 qualified 17.7 Example 3 1294 0.05 qualified 18.0 Example 4 1299 0.04 qualified 18.2 Example 5 1312 0.02 qualified 18.3 Comparative Example 1 1141 0.28 Failure 16.4 Comparative Example 2 1123 0.36 Failure 16.2
[0097] As can be seen from Table 1, the powder metallurgy shaft parts materials involved in the embodiments of the present invention have better mechanical properties, wear resistance, corrosion resistance and fatigue resistance than the comparative products, and the combined use of rhenium powder, osmium powder, nano-titanium nitride, cellulose nanocrystals, non-metallic powder, germanium powder, nano-chromium boride and trirosin acid glycerol is beneficial to improving the above properties.
[0098] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A powder metallurgy shaft parts material, characterized in that: The invention is made of the following components in weight percentage: 0.5wt%-1wt% manganese powder, 1wt%-2wt% copper powder, 0.1wt%-0.4wt% molybdenum powder, 1wt%-3wt% nickel powder, 0.03wt%-0.06wt% hafnium powder, 0.03wt%-0.06wt% rare earth powder, 0.001wt%-0.004wt% rhenium powder, 0.001wt%-0.003wt% osmium powder, 0.1wt%-0.3wt% vanadium powder, 0.01wt%-0.01wt% tantalum powder. t%-0.03wt%, cobalt powder 0.3wt%-0.5wt%, non-metallic powder 0.001wt%-0.003wt%, indium powder 0.01wt%-0.04wt%, germanium powder 0.01wt%-0.03wt%, gallium powder 0.05wt%-0.12wt%, nano-titanium nitride 0.01wt%-0.03wt%, nano-chromium boride 0.01wt%-0.03wt%, nano-tungsten carbide 0.01wt%-0.03wt%, and the balance is iron powder.
2. The powder metallurgy shaft parts material according to claim 1, characterized in that: The powder metallurgy shaft parts material also includes the following components in weight percentage: 0.01wt%-0.06wt% lubricant, 0.08wt%-0.12wt% cellulose nanocrystals, 0.05wt%-0.1wt% trirosin acid glycerol, and 0.1wt%-0.15wt% 1,3,5-triglycidyl-S-triazinetrione.
3. The powder metallurgy shaft parts material according to claim 2, characterized in that: The lubricant is zinc stearate.
4. The powder metallurgy shaft parts material according to claim 2, characterized in that: The fiber nanocrystals have a length of 100-500nm and a diameter of 20-100nm.
5. The powder metallurgy shaft parts material according to claim 1, characterized in that: The particle size of the manganese powder is 800-1200 mesh; the particle size of the copper powder is 1000-1300 mesh; the particle size of the molybdenum powder is 1200-1500 mesh; the particle size of the nickel powder is 800-1000 mesh; the particle size of the hafnium powder is 800-1200 mesh; the particle size of the rare earth powder is 1000-1300 mesh; the particle size of the rhenium powder is 900-1300 mesh; the particle size of the osmium powder is 1200-1400 mesh; the particle size of the vanadium powder is 1100-1400 mesh; and the particle size of the tantalum powder is 1000-1300 mesh.
6. The powder metallurgy shaft parts material according to claim 1, characterized in that: The particle size of the cobalt powder is 900-1300 mesh; the particle size of the non-metallic powder is 1200-1400 mesh; the particle size of the indium powder is 1100-1400 mesh; the particle size of the germanium powder is 1000-1300 mesh; the particle size of the gallium powder is 800-1000 mesh; and the particle size of the iron powder is 1000-1400 mesh.
7. The powder metallurgy shaft parts material according to claim 1, characterized in that: The particle size of the nano-chromium boride is 10-80nm; the particle size of the nano-titanium nitride is 20-90nm; and the particle size of the nano-tungsten carbide is 30-70nm.
8. The powder metallurgy shaft parts material according to claim 1, characterized in that: The non-metallic powder is a mixture of silicon powder, boron powder and tellurium powder in a mass ratio of 1:(0.8-1.2):(0.2-0.5); the rare earth powder is a mixture of scandium powder, yttrium powder and cerium powder in a mass ratio of 1:(1-2):(2-4).
9. A method for preparing a powder metallurgy shaft parts material according to any one of claims 1 to 8, characterized in that: The steps include: Step S1, putting each component into a mixer according to mass percentage and mixing them evenly to obtain a powder metallurgy mixed raw material powder; Step S2, loading the powder metallurgy mixed raw material powder into a mold, pressing to obtain a compact, and then sintering in a vacuum atmosphere; Step S3: After heat treatment, powder metallurgy shaft parts material is obtained.
10. The method for preparing powder metallurgy shaft parts material according to claim 9, characterized in that: The pressing pressure in step S2 is 280-530MPa; the sintering in step S2 is hot pressing sintering, the sintering temperature is 1220-1360°C, the holding time is 2-4h, and the pressure applied to the mold is 15-25Mpa; the heat treatment in step S3 includes quenching and tempering treatment performed in sequence; the quenching treatment is a two-stage quenching treatment, the temperature of the first stage quenching treatment is 700-750°C, the holding time is 30-45 minutes, the temperature of the second stage quenching treatment is 950-1100°C, the holding time is 1-2 hours, and oil cooling to room temperature; the temperature of the tempering treatment is 350-500°C, and the holding time is 1-3 hours.
Citation Information
Patent Citations
A powder metallurgy material for automotive shaft parts and its preparation method
CN103406532B
Powder metallurgy material and application thereof
CN117026056A
Powder metallurgy automobile part gear and preparation method thereof
CN117428193A
Compression-resistant powder metallurgy gear and preparation method thereof
CN118218597A
Powder metallurgy duplicate gear and preparation method thereof
CN118256822A